# expression manipulating

• Nov 17th 2011, 05:43 AM
Stuck Man
expression manipulating
I have done the first part and found the new limits but I can't do the last part.
• Nov 17th 2011, 05:49 AM
Prove It
Re: expression manipulating
Quote:

Originally Posted by Stuck Man
I have done the first part and found the new limits but I can't do the last part.

\displaystyle \displaystyle \begin{align*} y &= \frac{x}{1 + x^2} \\ \frac{y}{x} &= \frac{1}{1 + x^2} \\ \frac{x}{y} &= 1 + x^2 \\ \left(\frac{x}{y}\right)^2 &= (1 + x^2)^2 \\ \left(\frac{x}{y}\right)^2 &= 1 + 2x^2 + x^4 \\ \left(\frac{x}{y}\right)^2 - 2x^2 &= 1 + x^4 \end{align*}
• Nov 17th 2011, 06:23 AM
Stuck Man
Re: expression manipulating
I've done that part.
• Nov 17th 2011, 06:40 PM
Prove It
Re: expression manipulating
Quote:

Originally Posted by Stuck Man
I've done that part.

You're welcome ><
• Nov 18th 2011, 02:48 AM
tom@ballooncalculus
Re: expression manipulating
$\displaystyle \displaystyle{y = \frac{x}{1 + x^2}}$

And,

$\displaystyle \displaystyle{\frac{dy}{dx} = \frac{1 - x^2}{(1 + x^2)^2}}$

Therefore,

$\displaystyle \displaystyle{\frac{1 - x^2}{(1 + x^2) \sqrt{1 + x^4}}}$

$\displaystyle =\displaystyle{\frac{1 - x^2}{(1 + x^2) \sqrt{(\frac{x}{y})^2 - 2x^2}}}$

$\displaystyle =\displaystyle{\frac{1 - x^2}{(1 + x^2) \sqrt{(\frac{x}{y})^2 (1 - 2y^2)}}}}$

$\displaystyle =\displaystyle{\frac{1 - x^2}{(1 + x^2)\ \frac{x}{y} \sqrt{1 - 2y^2}}}$

$\displaystyle =\displaystyle{\frac{1 - x^2}{x(1 + x^2)}\ \frac{y}{\sqrt{1 - 2y^2}}}$

$\displaystyle =\displaystyle{\frac{1 + x^2}{x}\ \frac{y}{\sqrt{1 - 2y^2}}\ \frac{1 - x^2}{(1 + x^2)^2}}}$

$\displaystyle =\displaystyle{\frac{1}{y}\ \frac{y}{\sqrt{1 - 2y^2}}\ \frac{dy}{dx}}}$

$\displaystyle =\displaystyle{\frac{1}{\sqrt{1 - 2y^2}}\ \frac{dy}{dx}}}$